An Investigation Into Finding Effective Ways of Presenting a Written Source to Students. Issue 1 (1st December 2017) - Vella, Yosanne; Caruana, Kimberley
Abstract : Written historical sources can be quite challenging for students to analyse in secondary school. They are sometimes long and tedious to read as well as containing difficult and awkward text. The presentation of such sources by history teachers to their class has to be well thought out. This paper describes the various methods used to offer the same written source as historical evidence for analyses but in different formats to a class of 13/14 year olds. The written source was a letter taken from the textbook used by history students who will eventually be sitting for their SEC O Level history paper. The source can be found in their Maltese history textbook 'From the coming of the Knights to EU membership'. This letter is one of the most challenging sources in the textbook and this paper reports the endeavour to improve ways of teaching this written source to students. This source was used with two groups of history students and different techniques were used to make the source more palatable to the students and thus support their learning. Students' work was then evaluated from a worksheet given after the activities and this was contrasted with the answers to the same sheet of questions prior to the study. The students' work mostly improved and hence from these results, this paper makes recommendations about the possible best format to present written sources to students.